Dukungan Keluarga Berhubungan dengan Personal Hygiene pada Lansia di Wilayah Kerja Puskesmas Binanga - Thahirah, Thahirah; Sitta Pesihatu, Jumeiyanti Fajar; Rahmawati, Eka (Mando Care Jurnal, 2024)
Elderly refers to a condition where an organism has reached maturity in function and size and has undergone changes over time. Personal hygiene issues among the elderly often arise due to various physical, psychological, and environmental factors. Personal hygiene is a fundamental step in maintaining health, as a clean body can minimize the risk of contracting diseases, particularly those related to poor personal hygiene. The purpose of this study is to examine the relationship between family support and personal hygiene among the elderly in the Binanga Health Center working area. The research employed an analytical correlation design, emphasizing the relationship between variables or between independent and dependent variables. The study results indicate a significant relationship between family support and the personal hygiene of the elderly, as shown by the Chi-square test result with a p-value of 0.000 or α<0.05. This study demonstrates that elderly individuals who receive adequate physical, emotional, and informational support from their families tend to have better personal hygiene. These findings can serve as a foundation for developing elderly health programs, such as educating families on the importance of their support and role in maintaining the cleanliness of the elderly at the community level.